A Mixture of Acacia Bark Extract (Acacia mangium Willd) and Potassium Iodide as A Corrosion Inhibitor in Sulfuric Acid Solution - Gusti, Diah Riski; Gunawan, Anjelli Putri; Muhammad, Damris; Lestari, Intan (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
Corrosion is a decrease in the quality of a metal material caused by a reaction with the environment. Corrosion cannot be eliminated, but corrosion can be slowed down in several ways by adding corrosion inhibitors and synergistic effects. Acacia bark extract (Acacia mangium Willd) with the addition of 0.02 M KI has the potential as a corrosion inhibitor for steel because it contains secondary metabolites, so it can provide a synergistic effect and increase the value of inhibition efficiency on steel. This research aimed to analyze the effect of a mixture of acacia bark extracts (Acacia mangium Willd) with the addition of KI on inhibition efficiency corrosion of mild steel in sulfuric acid media. The method used in this study is the method of weight loss, adsorption isotherms, and thermodynamic parameters, which were carried out by varying the concentration of acacia bark extract and the immersion temperature of the steel. To strengthen the research results, characterization was carried out using FTIR and SEM. The results showed that the corrosion rate of mild steel immersed in 0.75 M H2SO4 corrosive medium with the addition of 0.02 M KI increased with increasing immersion temperature. These results are reinforced by the results of FTIR and SEM analysis which show that there is an interaction between mild steel and acacia bark extract (Acacia mangium Willd) and KI 0.02 M. Based on the thermodynamic parameters, the resulting values of ∆Hads, ∆Gads, and ∆Sads show that the adsorption process of acacia bark extract (Acacia mangium Willd) in corrosive medium H2SO4 0.75 M with the addition of 0.02 M KI took place spontaneously, showing the type of physical adsorption, adsorbed stable, the adsorption process was exothermic and the degree of irregularity in the adsorption process. The inhibition efficiency of acacia bark extract (Acacia mangium Willd) with the addition of 0.02 M KI was highest at 60 °C with an extract concentration of 2.5 g/L of 81%. The higher the immersion temperature, the greater the resulting synergistic effect